2022
DOI: 10.3390/foods11193142
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Edible Filamentous Fungal Carriers as Cell Supports for Growth of Yeast and Cultivated Meat

Abstract: The growth and activity of adherent cells can be enabled or enhanced through attachment to a solid surface. For food and beverage production processes, these solid supports should be food-grade, low-cost, and biocompatible with the cell of interest. Solid supports that are edible can be a part of the final product, thus simplifying downstream operations in the production of fermented beverages and lab grown meat. We provide proof of concept that edible filamentous fungal pellets can function as a solid support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
(56 reference statements)
1
12
0
Order By: Relevance
“…Molding refers to a method of molding a scaffold polymer to which cells are attached into a mold designed according to the researcher’s intention. This includes molds formed by 3D printing (not a bioprinter), decellularization, and freeze-drying, in the same sense, MC is also used for this belongs ( Ogawa et al, 2022 ). This scaffold has a relatively simple manufacturing method compared to other methods and is inexpensive because it can be used semi-permanently.…”
Section: Scaffold Production Methodsmentioning
confidence: 99%
“…Molding refers to a method of molding a scaffold polymer to which cells are attached into a mold designed according to the researcher’s intention. This includes molds formed by 3D printing (not a bioprinter), decellularization, and freeze-drying, in the same sense, MC is also used for this belongs ( Ogawa et al, 2022 ). This scaffold has a relatively simple manufacturing method compared to other methods and is inexpensive because it can be used semi-permanently.…”
Section: Scaffold Production Methodsmentioning
confidence: 99%
“…Such an observation was consistent with the previous reports of fungal pellets formed by P. chrysogenum H3 and other filamentous fungi. 14,22,34 With the pre-formed fungal pellets and pre-grown S. cerevisiae G1 yeast cells, curcumin was encapsulated using vacuum-facilitated infusion, resulting in the two encapsulation systems: FPc and YE-c. Subsequently, YE/FP-c was created by immobilizing the curcumin-loaded G1 yeast cells (YE-c) in the pre-formed H3 fungal pellet through a rapid internalization facilitated by the vacuum treatment.…”
Section: Microstructure Of the Multicellular Encapsulation Systemsmentioning
confidence: 99%
“…Recently, FF Aspergillus oryzae has been shown to be a good supporting material for the growth of both yeast and animal cells. 22 A yeast biocapsule, with the coattachment of Saccharomyces cerevisiae and FF Penicillium chrysogenum, is a well-studied system, especially for the applications of alcoholic fermentation, such as the production of wine, beer, and bioethanol. [23][24][25][26] FP and yeast-FF biocapsules served as perfect multicellular model systems to study the matrix effect of these encapsulation systems on the release of encapsulated bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have reported both pH decreases [14,45] and increases [46] during fungal-assisted immobilization of microalgae. Causes of the different results in the literature are not clear but may be strain specific and related to operational parameters such as fungal spore-assisted versus fungal pellet-assisted immobilization and/or the addition of glucose or other readily utilized carbon source during immobilization which might encourage secretion of organic acids by certain fungal strains [47]. Low pH has been reported to favor immobilization with certain strain combinations [45,47] but not others [46].…”
Section: Adsorption Isotherm and Kineticsmentioning
confidence: 99%
“…Causes of the different results in the literature are not clear but may be strain specific and related to operational parameters such as fungal spore-assisted versus fungal pellet-assisted immobilization and/or the addition of glucose or other readily utilized carbon source during immobilization which might encourage secretion of organic acids by certain fungal strains [47]. Low pH has been reported to favor immobilization with certain strain combinations [45,47] but not others [46]. Choi et al [46] noticed little impact of initial pH on the fungal pellet-assisted immobilization of Synechocystis sp.…”
Section: Adsorption Isotherm and Kineticsmentioning
confidence: 99%